Capacity Planning for Assembly Plant Unit PC1250 at Heavy Equipment Manufacturing Company - Anastasia Maukar; Rahman Ramadhan (TALENTA Publisher, 2026)
The rapid growth of Indonesia’s mining sector has triggered a critical capacity bottleneck on PT Komatsu Indonesia’s PC1250 production line. Current output is limited to 4 units per month compared to a projected demand of 7 units, resulting in an extreme overutilization rate of 256%. This study applies an Aggregate Planning strategy by comparing three methods: Transportation, Hybrid, and Excel Spreadsheet GRG, which were validated through the Master Production Schedule (MPS) and Rough-Cut Capacity Planning (RCCP). Analysis results show that the Excel GRG Method is the optimal solution with the lowest cost of IDR 132,649,508, more efficient than the Transportation Method (IDR 135,833,000) and the recruitment-focused Hybrid Method (IDR 403,365,672). Although current facility capacity is limited to approximately 1,461 hours (1,320 regular hours and 141 overtime hours), the optimal strategy bridges this gap by utilizing 1,408 regular hours, 395 overtime hours, and 1,383 subcontracted hours. This approach successfully meets the cumulative demand for 49 units without a backlog, reducing the utilization rate from 256% to a more sustainable 95%, thereby ensuring operational stability and maximum economic efficiency.